RENEWABLE ENERGY AND SUSTAINABLE DEVELOPMENT: EMERGING TRENDS AND TECHNOLOGIES - Engr Theo Aku Ugah; Prof. Okeke Gerald Ndubuisi; Engr. Prof Sony Emeka Ali; Associate Professor Cynthia Amaka R Obiorah Ph.D; Dr. Omatseyione Nesiama; Engr. Cletus Onyemhese Agbakhamen; Engr. Ogheneteme Pupu Okoro (IPHO-Journal of Advance Research in Science And Engineering, 2025)
The urgent need for sustainable energy solutions has intensified due to climate change, energy crises, and environmental degradation (IPCC, 2021). Traditional fossil fuels significantly contribute to greenhouse gas (GHG) emissions, necessitating a transition toward renewable energy sources such as solar, wind, hydro, and bioenergy (IEA, 2022). These alternatives offer potential solutions for energy security, carbon reduction, and economic sustainability. However, their extensive acceptance faces challenges, including technological limitations, economic barriers, and policy constraints (REN21, 2023).This study explores advanced renewable energy technologies and their role in achieving global sustainability. It assesses innovations in energy efficiency, integration of multiple renewable sources, and emerging storage solutions (Smil, 2020). Additionally, it examines economic and policy challenges that hinder large-scale deployment and proposes strategies for overcoming these barriers (Jacobson et al., 2017). The research highlights the importance of international cooperation and government policies in driving the transition toward a renewable energy future (Sovacool et al., 2018).Key research questions include evaluating the latest advancements in renewable energy, optimizing integration and storage, addressing economic and policy constraints, and understanding the role of renewables in achieving carbon neutrality. By analyzing these aspects, this study provides valuable insights for policymakers, researchers, and industry stakeholders to accelerate the adoption of renewable energy and enhance sustainability worldwide.